PENGARUH KINERJA KEUANGAN DAN FAKTOR LAINNYA TERHADAP MANAJEMEN LABA PADA PERUSAHAAN - Halim, Ezra Drata; Chrisnanti, Frestin (Pusat Penelitian dan Pengabdian kepada Masyarakat Sekolah Tinggi Ilmu Ekonomi Trisakti, 2023)
This research is a development of previous research, namely Asim and Ismail (2019) with the dependent variable earnings management and the independent variable leverage. This study aims to examine actual data on how financial performance and other variables affect earnings management in manufacturing organizations. Leverage, profitability, firm size, company growth, audit committee, fixed asset turnover, and audit quality are the factors used in this study. The population of this study is manufacturing companies listed on the Indonesia Stock Exchange during the period 2019 to 2021. Purposive sampling is used to choose the samples for this study, and 216 data are collected. Data were examined using several regression techniques. Proxy that used in this research was Modified Jones Model as proxy of dependent variable earnings management to calculate data. The findings of this study demonstrated that the company growth have an impact on earnings management. This showed that changes of total asset of in a company from year to year can affected the manager to do earnings management. While others, such as leverage, profitability, firm size, audit committee, fixed asset turnover, and audit quality, do not influence on earnings management.